Español - Español; Español; Español, (Ars Pharmaceutica (Internet), 1980)
In this paper we have studied the ecologic, chorologic and sintaxonomic behaviour of Lamium bifidum Cyr. subsp, bifidum in the Spain. A new association is described and also we enclose the distribution may of this taxon in the Spain.